Technical/economic/environmental optimal wind generation allocation in power systems - Abdelhay, Zeinb; Eladl, Abdelfattah; Mansy, Ibrahim I. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This paper proposes an optimization technique to find the optimal allocation of wind farms (WFs) in a transmission network considering several objectives associated with economic, losses, voltage profile, and environmental impact represented in the reduction of carbon emissions. The problem is solved on the basis of maintaining three constraints which are transmission line power limits, active/reactive power constrain, and bus voltage limits. The particle swarm optimization (PSO) algorithm and Newton-Raphson method for load flow analysis are utilized to solve the optimization problem as a whole. In this context, there are two wind turbines added to the transmission network and a matrix laboratory (MATLAB) has been devised to evaluate their performance with varying capacities at different locations in the system. The proposed approach has been validated on the modified IEEE 14-bus transmission system.